The Effect of Digital Marketing and Product Innovation on MSME Sales Performance in the Digital Economy Era - Titis Sri Wulan; Dewi Agustina Solihin; Putri Ayu Permata Devi; Saida Zainurossalamia ZA; Asnawati (PT Mattawang Mediatama Solution, 2025)
This study investigates the effects of digital marketing capability and product innovation capability on sales performance among Indonesian micro, small, and medium enterprises (MSMEs) in the digital economy era. Using a quantitative, explanatory design, data were collected through a structured survey of MSME owners/managers and analyzed using ordinary least squares (OLS) regression in EViews. Sales performance was operationalized as a sales-oriented metric suitable for econometric estimation, while digital marketing and product innovation were measured as composite indices derived from Likert-scale items capturing routine execution and renewal intensity. Classical assumption diagnostics were conducted to support valid inference, including residual normality, heteroskedasticity, and multicollinearity checks; where needed, White robust standard errors were applied to address heteroskedasticity. The results demonstrate that both digital marketing capability and product innovation capability have positive and statistically significant relationships with MSME sales performance. Digital marketing capability shows a slightly stronger estimated effect, indicating that consistent digital routines—such as channel orchestration, content discipline, responsive customer interaction, and basic performance monitoring—are closely linked to improved sales outcomes. Product innovation capability also contributes significantly, suggesting that continuous renewal through quality improvement, new variants, and packaging/design enhancements strengthens differentiation and supports sales growth. The findings imply that MSME competitiveness in digital markets is best supported by integrating market-facing execution (digital marketing) with value reinforcement (product innovation), rather than relying on platform adoption alone. Practically, MSMEs should institutionalize measurable digital marketing processes while embedding structured innovation cycles that convert market feedback into product renewal. Policymakers and support institutions should prioritize capability-building programs tied to measurable performance outcomes. Future research may extend this model using longitudinal data and sector-specific moderators to capture delayed innovation effects and sustainability of sales gains. Keywords: digital marketing capability; product innovation capability; sales performance; MSMEs; digital economy; Indonesia.